QARAQALPAQ ESSE TEKSTLERINDEGI FONETIKALÍQ BIRLIKLERDIŃ STILLIK ózgeshelikleri - Mırzabaev, S. (SCIENCE and SOCIETY, 2025)
In this article, we get information about the genre variations of essay texts, subjective and objective emotional-expressiveness of the author and the characters in the works, as well as the current state of the language by studying the phonostylistic elements in the essay texts, which are a genre of Karakalpak literary journalism.
Keywords: stylistics; phonostylistics; phonographic-tools; alliteration; assonance; onomatopoeia; acromonogram; geminacy; essay